OS07.2.A Evaluation of Intraoperative Surgical Adjuncts and Resection of Glioblastoma (ELISAR GB): A UK and Ireland multicentre, prospective observational cohort study. (5th September 2022) - Solomou, G; Gharooni, A; Whitehouse, K; Poon, M T C; Piper, R J; Fountain, D M; Khan, D Z; Lopez, C C; Ooi, S Z; Lammy, S; Maqsood, R; Brochert, R J; et al.
Abstract: Background: Despite operative and adjuvant therapies, glioblastoma remains incurable, with the extent of resection being one of few treatments that can improve survival. To improve resection, operative adjuncts are used, with neuronavigation and 5-aminolevulinic acid (5-ALA) recommended as a standard of care in those aimed for maximal safe resection. Despite the standards, meta-analysis concluded that the impact of 5-ALA on the extent of surgical resection is of low quality due to bias in reporting tumour location and additional image guidance used, factors impacting on extent of resection as well as short-term neurological outcomes being uncertain. Therefore we aimed to evaluate the availability and use of 5-ALA and other adjuncts and compare surgical outcomes of 5-ALA-guided versus non-5-ALA-guided resections. Material and Methods: A multicenter prospective observational cohort study was conducted across 27 out of 31 available centres in the UK and Ireland from 6 January until 19 March 2020. Inclusion criteria included adults with first diagnosis, supratentorial glioblastoma undergoing resection. Primary outcomes included: i) the availability and use of surgical adjuncts and ii) complete resection of enhancing tissue (CRET). Secondary outcomes included adverse events, new onset of postoperative neurological deficit and post-operative neurological function. Descriptive and inferential statistics were used for analysis with a p-value <0.05 deemed significant. Results: 232 consecutive cases were identified. 142/232 cases were aimed for maximal safe resection subsequently divided into 5-ALA-guided (n=92) versus non-5-ALA-guided (n=50) resections. 5-ALA and neuronavigation were available across all centres. Neuronavigation and 5-ALA were used in 91% (n=129/142) and 65% (n=92/142) of cases aimed for maximal safe resection whereas 83% (n=75/90) and 49% (n=44/90) for debulk surgery. 35 unique combinations of surgical adjuncts were used in 232 operations. 5-ALA-guided resection yielded a higher percentage of CRET than without (55% versus 28%, p < 0.01). The two groups showed no difference in adverse events (p=0.98), new onset of neurological deficit (p=0.88) nor neurological function (p=0.7). A logistic regression analysis showed that 5-ALA was an important predictor of CRET regardless of additional adjuncts used (OR 2.4, CI 0.96-5.97, P = 0.05), tumour location and molecular characterisation (OR 3.48, CI 1.61-7.51, P <0.01). Conclusion: Firstly, we showed that 5-ALA is not always used for glioblastoma aimed for CRET. Secondly, we report a great heterogeneity of adjuncts used for resection, possibly explained by a lack of high-quality evidence and surgeon training. Thirdly we demonstrate that 5-ALA-guided resection leads to higher percentage of CRET regardless of other adjuncts used, tumour location and molecular characterisation.